Anti-phase boundary energy of β series precipitates in Mg-Y-Nd system. (1st March 2021) - Guo, Yanlin; Liu, Bin; Xie, Wei; Luo, Qun; Li, Qian
Abstract: Anti-phase boundary energy (APBE) is a vital contributing factor for the dislocation shearing mechanism which operates in Mg-RE alloys. To clarify the structure and composition dependence of APBE and provide the guidance for strength improvement of Mg alloys, the formation energy, misfit strain, and APBE of β series precipitates in Mg-Y-Nd system are investigated by first-principles calculations. The atomic occupations of ternary precipitates are determined based on misfit strains. The APBEs of β p ″ ′ phases are higher than that of β s ′, and precipitates in Mg-Nd system possess higher APBEs than their counterparts in Mg-Y system. The higher APBEs enable larger strength increments of precipitates in Mg-Nd system than Mg-Y system when the amount of Y and Nd are the same. However, when both elements reach their solubility limit, the large amount of Y makes up the low APBE and achieves superior strength increment than the precipitates in Mg-Nd system. Graphical abstract: Image, graphical abstract